2009
DOI: 10.1016/j.bmc.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal bivalent ligands for the estrogen receptor: Design, synthesis, characterization and binding affinities

Abstract: Steroidal bivalent ligands for the estrogen receptor (ER) were designed using crystal structures of ERα dimers as a template. The syntheses of several 17α-ethynylestradiol-based bivalent ligands with varying linker compositions and lengths are described. The binding affinities of these bivalent ligands for ERα and ERβ were determined. In the two series of bivalent ligands that we synthesized, there is a clear correlation between linker length and binding affinity, both of which reach a maximum at the same teth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…Since then several other groups have published bivalent or dimeric steroid syntheses using a variety of linkers [27, 28, 29, 30], but these papers focused on design, synthesis and/or binding, with little to no characterization of relative efficacy, potency or specificity. More recently, the Katzenellenbogen laboratory, publishers of the original manuscript on the synthesis of bivalent hexestrols, extended these studies with bivalent estrogen designs that displayed variable estrogen receptor binding affinities that correlated with linker length [31]. These estrogen dimers were evaluated comprehensively with respect to linker composition, tether length and receptor binding, but did not evaluate biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Since then several other groups have published bivalent or dimeric steroid syntheses using a variety of linkers [27, 28, 29, 30], but these papers focused on design, synthesis and/or binding, with little to no characterization of relative efficacy, potency or specificity. More recently, the Katzenellenbogen laboratory, publishers of the original manuscript on the synthesis of bivalent hexestrols, extended these studies with bivalent estrogen designs that displayed variable estrogen receptor binding affinities that correlated with linker length [31]. These estrogen dimers were evaluated comprehensively with respect to linker composition, tether length and receptor binding, but did not evaluate biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, we modeled the structure of a bivalent steroidal ligand published by LaFrate et al [22], where an EG5 spacer connects two E 2 s modified at the 17a position. Our data (not shown) suggests that this bivalent ligand also suffers from a drop in end-to-end distances (measured at the C17 positions) to a mean value distinctly below 10 Å .…”
Section: Resultsmentioning
confidence: 99%
“…During the last two decades, several bivalent ER ligands, composed of two individual ligands linked by flexible tethers, have been designed and synthesized [4,10,22]. In 2010, Wendlandt et al showed the biological activity of synthetic bivalent estrogen dimers linked by aliphatic spacers to be higher than that of 17b-estradiol [33].…”
Section: Bivalent Inhibition Of Estrogen Receptormentioning
confidence: 99%
“…Another very ancient receptor is the estrogen receptor (ER) (5), and John Katzenellenbogen (University of Illinois, Urbana) pointed out that compounds of diverse structure having a phenolic back-bone can function as estrogens (6). Although many compounds can activate ERs, tissue selectivity is conferred by tissue-specific activation of different effector gene networks.…”
Section: Evolution Of Nr Specificitymentioning
confidence: 99%